Incidence and Determinants of Acute Diarrhoea in Malaysia: A Population-based Study - Gurpreet, K; Tee, GH; Amal, NM; Paramesarvathy, R; Karuthan, C (Journal of Health, Population and Nutrition, 2011)
Acute diarrhoea is a major health problem in many parts of the world, contributing to about 1.8 million deaths globally. The objectives of the study were to assess the incidence, determinants, and severity of acute diarrhoea in the population. A nation-wide cross-sectional survey involving about 57,000 respondents was conducted via face-to-face interview among eligible respondents of all ages. An acute diarrhoeal episode was defined as having three or more episodes of loose stools in any 24-hour period within the past four weeks before the interview. The severity was measured by duration of acute diarrhoea and associated symptoms. The variables tested as determinants were age, sex, ethnicity, the highest educational level, total monthly household income, and locality. Univariate, bivariate and multivariate procedures meant for complex study design were used in the analyses. The four-week incidence of acute diarrhoea was 5% [95% confidence interval (CI) 4.8-5.2]. The incidence of acute diarrhoea among the estimated population was the highest among young adults aged 20-29 years, Other Bumiputras (the pre-dominant ethnic group in East Malaysia), those with tertiary-level of education, those earning a monthly household income of less than RM 400, and rural dwellers. Only age, ethnicity, the highest level of education attained, and locality were significantly associated with acute diarrhoea in bivariate analysis. In multivariate analysis, these four variables were found to be the determinants of acute diarrhoea. Sex and monthly household income were excluded from the model. The mean duration of acute diarrhoea was 2.0 days (standard deviation 1.3). Forty-six percent of the respondents reported stomach cramps as an associated symptom. The findings revealed that acute diarrhoea is still a major public-health concern in Malaysia and grossly undernotified. There is a need for intensification of public-health intervention efforts to reduce the incidence of acute diarrhoea while improving surveillance and notification of the disease. Key words: Cross-sectional survey; Diarrhoea, Acute; Sociodemographic factors; Malaysia DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7814 J HEALTH POPUL NUTR 2011 Apr;29(2):103-112